Exploring Entrepreneurial Sustainability: Trends, Drivers, and Future Directions - Yuni Ekawarti; Kristian Chandra; Lisa Hermawati; Iing Lukman; Azli Fahrizal (Sinergi International Journal of Economics, 2026)
Introduction: Entrepreneurial sustainability has emerged as an important research domain that integrates entrepreneurship with environmental, social, and economic sustainability objectives. Despite the growing number of publications, previous bibliometric studies remain fragmented, limited in temporal coverage, and provide insufficient understanding of the intellectual structure, thematic evolution, and future research directions of entrepreneurial sustainability. Methods: This study employed a Systematic Literature Review (SLR) combined with bibliometric analysis following the PRISMA framework. Data were collected from the Scopus database, yielding 1,932 publications, which were systematically screened to obtain 876 eligible articles. Bibliometric mapping was conducted using VOSviewer through keyword co-occurrence, overlay visualization, and density visualization to identify research themes, intellectual structures, and emerging trends. Results: The bibliometric analysis identified 8 major thematic clusters representing the intellectual structure of entrepreneurial sustainability research. Sustainability, circular economy, digital transformation, and supply chain management emerged as the dominant research themes. Overlay visualization revealed a significant shift from conceptual sustainability toward digital transformation, sustainable, and business performance in recent years, particularly in developing countries. Density visualization further indicated that sustainable finance, eco-tourism, international entrepreneurship, and creative industries remain underexplored research areas, presenting opportunities for future investigation. Conclusion: Entrepreneurial sustainability has evolved into an increasingly interdisciplinary research field driven by digitalization and sustainability transitions. This study contributes by providing a comprehensive bibliometric overview of research evolution over three decades and identifying emerging themes and research gaps. The findings offer valuable guidance for researchers, policymakers, and practitioners in developing evidence based strategies and future research agendas to promote sustainable entrepreneurship.